FAKTOR DURASI MENDERITA DM TIPE 2 MEMPENGARUHI PERUBAHAN KEMAMPUAN EFIKASI DIRI - Nurul Kartika Sari; Rivan Firdaus (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2020)
Background: Diabetes Mellitus (DM) cases increased by 776 cases from the previous year based on data from Abdul Wahab Sjahranie Regional Hospital. There are many changes that occur in the life of people with type 2 diabetes, such as stress, anxiety, anger, and feeling useless. These problems can be minimized if the patient also has the knowledge and ability as well as good self-efficacy to manage the disease by doing self-care. Aim: To analyze the factors associated with the self-efficacy of type 2 DM patients. Methods: a quantitative study with a cross sectional approach. The purposive sampling technique for Type 2 DM patients at Abdul Wahab Sjahranie Hospital Samarinda, totaling 60 respondents from September-October 2018. Results: showed a significant relationship between duration of suffering and self-efficacy of DM patients with a p value <0.001, and there was no significant relationship between age, sex, education level, knowledge, motivation and self-efficacy with a p value> 0.001. Conclusion: The duration of type 2 diabetes is related to the patient's self-efficacy ability.